SEMIOTIKA MORRIS DAN TRADISI PENAFSIRAN ALQUR’AN: SEBUAH TAWARAN TAFSIR KONTEKSTUAL - Ali Romdhoni (UIN Raden Mas Said Surakarta, 2016)
This paper offers an interpretation approach which involves historical data as its important dimension, socio-cultural contexts, and psychological effect on the audience. It is an important thing, since the Qur’anic interpretation studies in the contemporary era demands an interpretation model which involves historical data, socio-cultural context and psychological effect on the society. Since, the holy Qur’an given to Prophet Muhammad SAW was revealed in order to respond certain social condition, so each verse given to the prophet was clearly interrelated actively to the space and time. Hereby, each verse of the holy Qur’an has its own historical context, meaning, and effect.